2001
DOI: 10.1055/s-2001-12873
|View full text |Cite
|
Sign up to set email alerts
|

4-day triple therapy with rabeprazole, amoxicillin and clarithromycin in the eradication of Helicobacter pylori in patients with peptic ulcer disease - - A pilot study - -

Abstract: A 4-day triple therapy of rabeprazole in combination with clarithromycin and amoxicillin seems to be highly effective in eradicating H. pylori and well tolerated in patients with gastric and duodenal ulcer disease. The achieved eradication rate of 90% is comparable with the established 7-day triple therapy regimens. On the basis of these results and considering costs, side effects and compliance a large number of patients should be enrolled in a confirmatory 4-day eradication trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
1
Order By: Relevance
“…Small studies in non‐US populations describe 1‐, 2‐, 3‐, 4‐ and 5‐day treatment strategies. However, the results are variable, and many of the studies are small and therefore likely to exaggerate the success of the regimen 3–12 . Some studies have suggested that short treatment regimens may be effective in patients with ulcer disease, but that eradication percentages may be poorer in patients with H. pylori infection without ulcer disease and that these patients may require longer courses of therapy 13, 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Small studies in non‐US populations describe 1‐, 2‐, 3‐, 4‐ and 5‐day treatment strategies. However, the results are variable, and many of the studies are small and therefore likely to exaggerate the success of the regimen 3–12 . Some studies have suggested that short treatment regimens may be effective in patients with ulcer disease, but that eradication percentages may be poorer in patients with H. pylori infection without ulcer disease and that these patients may require longer courses of therapy 13, 14 .…”
Section: Introductionmentioning
confidence: 99%
“…2 In addition, rabeprazole was shown to have a more rapid onset of action and greater antisecretory activity than those of omeprazole and other PPIs in the inhibition of acid secretion. 8,9 One group of authors 10 showed that 4-day triple therapy with rabeprazole, amoxicillin, and clarithromycin achieved an eradication rate of 90%, comparable to that of a 7-day triple therapy regimen.…”
mentioning
confidence: 99%
“…Short‐term triple therapy is not regularly used for H. pylori treatment because of the inconsistency in the reported eradiation rates; however, this may be partly due to the failure to report the CYP2C19 genotypes of the subjects [5–7, 34–36]. The successful H. pylori eradication in CYP2C19 PMs seen in the present study suggests the possible use of short‐term triple therapy in such patients.…”
Section: Discussionmentioning
confidence: 65%
“…Nonetheless, short‐term (i.e. <7 days) triple therapy has been reported to increase patient compliance and reduce costs and adverse effects [5–7], but the evidence is limited and the rationale needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%